Effect of Combination of Infrared Knee Therapy with Ear Acupuncture and Local Point Electroacupuncture on Pain Scale in Knee Pain Patients at Puskesmas Baki Sukoharjo - Syamila, Fathia Dini; Sumanto; Muthiah, Nurmila; Eka Putri, Kurnia (Indonesian Journal of Acupuncture, 2025)
Joint disorders are common in the knee and result in pain and limitation of motion. Knee pain can signi-ficantly reduce people's quality of life. This disorder can be complained of starting from a productive age to the elderly. The etiology of knee pain is complex, one of which is the age factor. Acupuncture therapy can reduce several cases of musculoskeletal disorders, one of which is knee pain. This study aims to determine the effect of a combination of knee infrared therapy with ear acupuncture and local point electroacupuncture on the pain scale in knee pain patients at Puskesmas Baki Sukoharjo. This study used a type of quantitative research with a “Quasi-Experimental” research design. This study was divided into two treatment groups, namely the first group of ear acupuncture therapy combined with knee infrared, and the second group of local point electroacupuncture. This study started from February to March 2025 for 4 weeks and was conduct¬ed at Puskesmas Baki Sukoharjo. The results of the Wilcoxon test obtained a ρ value of 0.001, and the Mann-Whitney test obtained a ρ value of 0.011. These results indicate that there is an effect of a combination of knee infrared therapy with ear acupuncture and local point electroacupuncture on the pain scale in knee pain patients at Puskesmas Baki Sukoharjo. This means ear acupuncture therapy combined with knee infrared and local point electroacupuncture on knee pain cases showed significant results in reducing the pain scale (VAS) in patients at Puskesmas Baki Sukoharjo.